EFEKTIFITAS DOSIS ACTINOKOMPOS TERHADAP PENYAKIT LAYU FUSARIUM DAN PERTUMBUHAN TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Djaya A.A.; Supriati L.; Noor S. M. (Fakultas Pertanian Universitas Palangka Raya, 2015)
Fusarium wilt of tomato caused by a soil borne pathogen Fusarium oxysporum f.sp lycopersici which is an important disease in tomato plants in Indonesia and the world that led to the loss of tomato production in many regions due to rapid wilting process that occurs in young and old plants and cause a yield loss of up to 30%-50%. The purpose of research to determine the effectiveness of the dosages of actinocompost against fusarium wilt disease and the response to the growth of tomato plants has been carried out in the laboratory and screenhouse of Department of Agriculture, Faculty of Agriculture, University of Palangkaraya, September to December 2012. The research design used completely randomized design with six replications with five 5 level dose of actinokompos consists of: Ao (without compost or control), A1 (10 g compost polybag-1), A2 (20 g compost polybag-1), A3 (30 g polybag compost-1), A4 (40 g compost polybag-1). Observations included: (1) disease intensity, (2) the effectiveness of antagonist, (3) plant height and stem diameter of tomato at 3, 4, 5 weeks after planting (wap). Conclusions from this research show that (1). Applyed of actinocompost suppresing the intensity disease of fusarium wilt on tomato plants, increased plant height at 3-4 wap, increased the diameter of the plant stem at 3-5 wap, effectiveness of antagonist was execellent, (2). Applying actinocompost at 10 g plant-1 is more efficient than other treatments because suppressed fusarium wilt intensity of 0% and the effectiveness of the antagonist has a very good value (> 69%).